The genetics of intra‐ and interspecific competitive response and effect in a local population of an annual plant species. (3rd April 2015) - Baron, Etienne; Richirt, Julien; Villoutreix, Romain; Amsellem, Laurent; Roux, Fabrice
Summary: While competition is recognized as a major factor responsible for plant community dynamics, the genetics of intra‐ and interspecific competitive ability of a target species (i.e. level of intra‐population genetic variation, identity of phenotypic traits under selection and genetic bases) still deserves a deeper investigation at the local spatial scale by considering both numerous genotypes and several interacting species. In this study, we tested whether the genetics of competitive response and effect in Arabidopsis thaliana was dependent on the competitive environment at both the intraspecific and interspecific levels. We used a mapping population of 48 accessions (i) that maximize the genetic diversity of a local population of A. thaliana and (ii) that have been genotyped for 168 503 single nucleotide polymorphisms. In a common garden experiment, those 48 accessions were grown in six competitive environments: the absence of competition, intraspecific competition and interspecific competition with four species frequently associated with A. thaliana in natural plant communities ( i.e. Poa annua, Stellaria media, Trifolium repens and Veronica arvensis ). A suite of nine phenotypic traits, including a proxy of fitness, were scored on each target A. thaliana plant and the above‐ground dry biomass of its corresponding competitor was estimated. We first showed that crossing reaction norms of competitive response ( A. thaliana performance) and effect (competitor biomass) might promote maintenance of genetic variation in a local population of A. thaliana and species coexistence at a fine spatial scale. By estimating genotypic gradients of selection, we then demonstrated that the optimal phenotypic strategies in response to competition depend on the identity of the competitor species. Finally, a genomewide association mapping approach highlighted that genomic regions associated with direct genetic effects were (i) dependent on the competitor species and (ii) different from genomic regions associated with interspecific indirect genetic effects. While a first step, this study highlighted the power of adding ecology to genomics in A. thaliana to identify genetic bases underlying micro‐geographic adaptation to competition. Next‐generation sequencing technologies will undoubtedly facilitate the discovery of molecular and genetic mechanisms underlying competitive ability in other plant species, and thereby the prediction of evolutionary trajectories of plant communities. Abstract : Lay Summary